Prevalence of Overweight and Obesity Among Adult Women in China, Mali and United States: Evolution of Trends over Ten Years. (29th May 2020) - Traore, Stanislav Seydou; Amoah, Adwoa Nyantakyiwaa; Chen, Huanan; Cao, Yuan; Qiu, Yanfang; Zhang, Han; Hu, Youchun; Fu, Rong; Lyu, Quanjun
Abstract: Objectives: This article assessed trends in the prevalence of overweight and obesity over ten years among adult women. Methods: A cross-sectional study was conducted using National Surveys Data from China, Mali and the United States between 2001–2002 and 2012–2013. The sample population consisted of all adult women: 140, 022 (2002) and 157, 850 (2012) adults aged 18 and above in China, 10, 424 (2002) and 4502 (2012) women aged 15–49 in Mali, 4413 (2001) and 5181 (2012) adults aged 20 and above in the USA. The proportion test (Z test) was used to evaluate the 10-year prevalence differences in different countries. Results: In ten-year period, overweight has significantly increased from 22.7% to 29.9% among Chinese women with a growth of 7.2% ( P -value < 0.05) and, 11.2% to 12.9% in Malian women with a growth of 1.7% ( P -value < 0.05). Among US women, overweight has increased from 28.2% to 29.7% with a non-significant growth of 1.5% ( P -value >0.05). The prevalence of women's obesity in all three countries has significantly increased, more particularly in China. Conclusions: Data from the National Survey over ten years showed an increase in the prevalence of overweight as well as obesity in Chinese, Malian and US women. Funding Sources: This work was supported by the National Natural Science Foundation of China [Project number 81, 673, 165].